SOFT SKILLS IN THE DIGITAL ERA: ROLES OF VILLAGE HEALTH VOLUNTEERS (VHV) 4.0 - ยืนยง, พันธะกานต์ (Primary Health Care Journal (Northeastern Edition), 2025)
This academic article analyzes the development of soft skills in Village Health Volunteers (VHVs) 4.0, defining these skills as a key competency for enhancing health work potential in the digital age, where technology and innovation are integral to the community health service system. Employing an analytical literature review, this study synthesizes relevant research and academic documents to identify soft skills essential for adaptability, communication, and the management of local health work. The synthesis indicates that key soft skills for VHVs 4.0 comprise five main dimensions: 1) creativity and innovation for problem-solving and the appropriate use of technology; 2) strategic communication and persuasion to promote technology adoption and disseminate health knowledge; 3) effective collaboration grounded in trust, empathy, and shared leadership; 4) flexibility and adaptability to change to meet modern demands and increase work efficiency; and 5) time and personal resource management to balance community missions with self-development. Therefore, the development of VHVs 4.0 should focus on enhancing both psychosocial capital and lifelong learning to transform these soft skills into sustainable human capital. Promoting spiritual values (e.g., compassion, acceptance, and mutual assistance) will lay the foundation for a learning community capable of integrating digital technology to enhance health work effectively and sustainably.